2017
DOI: 10.4103/jovr.jovr_104_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two scheimpflug anterior segment analyzers

Abstract: Purpose:To compare the anterior segment indices measured by two Scheimpflug camera machines; Galilei and Pentacam.Methods:In this observational case series, the anterior segment indices of myopic healthy subjects seeking for refractive surgery were measured by Pentacam and Galilei on the same day. Analyzed parameters were anterior and posterior best fit spheres (BFS), axial curvature, true corneal power, central corneal thickness (CCT), anterior chamber (AC) depth, AC volume, AC angle, and pupil diameter.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
(33 reference statements)
0
9
1
Order By: Relevance
“…Its significance cannot be overstated, as evidenced by several studies that compared it using various Scheimpflug corneal imaging devices [ 29 , 30 ]. While some studies report that these devices are interchangeable and yield differences that fall within clinically acceptable levels, [ 14 , 22 , 25 , 31 ] others, such as Anoyal et al, [ 13 ] have found significant differences in ACD findings. The authors issued a cautionary note regarding the interchangeable use of these instruments, highlighting the potential for miscalculations in intraocular lens (IOL) power due to substantial disparities in ACD measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Its significance cannot be overstated, as evidenced by several studies that compared it using various Scheimpflug corneal imaging devices [ 29 , 30 ]. While some studies report that these devices are interchangeable and yield differences that fall within clinically acceptable levels, [ 14 , 22 , 25 , 31 ] others, such as Anoyal et al, [ 13 ] have found significant differences in ACD findings. The authors issued a cautionary note regarding the interchangeable use of these instruments, highlighting the potential for miscalculations in intraocular lens (IOL) power due to substantial disparities in ACD measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies have compared correlation and agreement of SimK measurements between the devices we investigated and other newer or older technologies, including IOLMaster 500, Pentacam XL, Verion imaging guiding system, and Sirius Scheimpflug–Placido topographer [ 1 , 9 14 ]. Similar to our study, a recent prior study evaluated the repeatability and comparability of the IOLMaster 700 with the Galilei G4 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Baradan-Rafii et al [ 32 ] compared the anterior segment indices, including CT, measured by two Scheimpflug devices, Pentacam and Galilei in 176 eyes of 88 participants: mean central corneal thickness obtained with Galilei was significantly thicker than that one measured by Pentacam, with a range of 95% of limit of agreement (-62 to -31 μm) too wide. For this reason, the authors did not suggest to use the two systems interchangeably.…”
Section: Discussionmentioning
confidence: 99%